Voices behind the front desk: A triangular lens on English competence in hospitality education - Hamdan Anwari; Bambang Widi Pratolo; Dwi Sulisworo (English Language Teaching Educational Journal, 2026)
The hospitality industry, as a linguistically and culturally charged domain, demands communication that extends beyond grammatical correctness toward adaptive, service-oriented performance. This study investigates the state of English competence among vocational hospitality students in Yogyakarta by integrating perspectives from three key stakeholders i.e.,  students, lecturers, and industry practitioners. The research adopts a mixed-methods design to uncover the alignment and dissonance between classroom instruction, communicative readiness, and workplace expectations. Quantitative data from 86 student respondents reveal that over 80% face persistent challenges in spontaneous English interaction, citing limited vocabulary, hesitation, and low confidence. Complementary qualitative insights from focus group discussions with five lecturers and interviews with twelve hotel professionals illustrate that English proficiency in hospitality is increasingly perceived as a form of professional capital: a synthesis of linguistic agility, intercultural empathy, and emotional intelligence. The findings highlight the inadequacy of conventional, grammar-driven ESP pedagogy and advocate for a transformative, partnership-based learning model that embeds authentic industry participation, simulation-driven practice, and performance-based evaluation. The study contributes to ongoing discussions in English for Specific Purposes (ESP) by reframing communicative competence as a professional, affective, and intercultural construct rather than a linguistic artifact. It argues that recontextualizing English learning through design thinking and work-integrated learning principles can foster communicative resilience, industry alignment, and global employability among vocational graduates.